Desain Responsif dan Dampaknya terhadap Pengalaman pengguna di Situs E-Commerce - Olivia, Melvina (Jurnal Komputer, 2025)
The development of information technology today has significantly changed the view of business, especially in e-commerce. Companies engaged in the food sales industry such as a shop are urgently needed to increase the effectiveness of online promotion and sales through redesigning e-commerce websites. This research aims to design an e-commerce website that combines attractive design elements, functionality, and effective promotional strategies to improve branding and marketing. The methodology used in this research includes surveys, interviews, and competitor analysis to understand user needs and current industry trends. The results show that increasing the effectiveness of online promotion and sales requires strategic integration between three main elements, namely attractive and responsive design, intuitive and user-friendly functionality, and targeted and effective promotional strategies. Based on the research results, an e-commerce website design, which combines several elements, with a focus on an attractive user experience and an easy purchasing process. The implementation of this design in the future can increase branding visibility, optimise user experience.